Technique and coordination of the front crawl swimming stroke - Demarie, S.; Guidotti, F.; Minganti, C.; Paserini, A.; Nagni, G. (Medicina dello Sport, 2023)
BACKGROUND: The link between asymmetries and swimming performance has been highlighted. Propulsion asymmetries may also increase injury rates. Aim of the present study was to assess upper limb asymmetries in the front crawl stroke of elite and youth competitive male and female swimmers.